Clinical profile and determinants of mortality in patients with interstitial lung disease admitted for COVID-19 - Mulet, Alba; Núñez-Gil, Iván J.; Carbonell, Juan Antonio; Soriano, Joan B.; Viana-Llamas, María C.; Raposeiras-Roubin, Sergio; Romero, Rodolfo; Alfonso-Rodríguez, Emilio; Uribarri, Aitor; Feltes, Gisela; Becerra-Muñoz, Victor M.; Santoro, Francesco; et al. (Journal of Clinical Medicine, 2023)
Background: Concern has risen about the effects of COVID-19 in interstitial lung disease (ILD) patients. The aim of our study was to determine clinical characteristics and prognostic factors of ILD patients admitted for COVID-19. Methods: Ancillary analysis of an international, multicenter COVID-19 registry (HOPE: Health Outcome Predictive Evaluation) was performed. The subgroup of ILD patients was selected and compared with the rest of the cohort. Results: A total of 114 patients with ILDs were evaluated. Mean ± SD age was 72.4 ± 13.6 years, and 65.8% were men. ILD patients were older, had more comorbidities, received more home oxygen therapy and more frequently had respiratory failure upon admission than non-ILD patients (all p < 0.05). In laboratory findings, ILD patients more frequently had elevated LDH, C-reactive protein, and D-dimer levels (all p < 0.05). A multivariate analysis showed that chronic kidney disease and respiratory insufficiency on admission were predictors of ventilatory support, and that older age, kidney disease and elevated LDH were predictors of death. Conclusions: Our data show that ILD patients admitted for COVID-19 are older, have more comorbidities, more frequently require ventilatory support and have higher mortality than those without ILDs. Older age, kidney disease and LDH were independent predictors of mortality in this population.
Gesehen am 30.09.2024